An Identification of Physics Pre-Service Teachers' Science Process Skills Through Science Process Skills-Based Practicum Guidebook - Darmaji, Darmaji; Kurniawan, Dwi Agus; Suryani, Ai; Lestari, Ayu (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2018)
This research was conducted to identify the science process skills of the physics education students of Jambi University in prism refraction practicum after using the basic physics practicum guidebook II. This research is a quantitative descriptive method. The study was conducted with a sample of 91 students. Data collection techniques were carried out using a science process skill observation sheet which was supported by interviews and documentation. Data were analyzed using descriptive statistics. The results showed that most students are highly skilled in implementing science process skills-based practicum with the following percentages: observing by 48.35%, classifying by 38.46%, measuring by 39.56%, predicting by 58.64%, compiling data tables by 51.65%, making graph by 58.24%, planning the experiment by 61.54%, and conducting the experiment by 45.05%. The students were also quite skilled in constructing hypotheses and defining variables with the percentage of 57.14% and 39.56%, respectively. The results of the study are expected to be used as a consideration for study programs and other faculties at Jambi University as well as other universities to conduct related studies.